Psycholinguistic Analysis of Religious Communications in Times of Creation Orthodox Church of Ukraine - Kostruba, Natalia (Psychological Prospects Journal, 2019)
The article analyzes the religious communications in times of creation Orthodox Church of Ukraine. The interpretation of religious communication and its main characteristics are highlighted. The article contains the main features of religious media, the benefits of religious Internet communications. An overview of the Ukrainian Orthodox Church (Moscow Patriarchate) (UOC-MP) printed publications is conducted. The basic four stages of frame analysis of the text are described, which also contains a characteristic of elaborating the scenarios of the text. Framing analysis was made by using the materials of Statement of the Holy Synod of the Ukrainian Orthodox Church (UOC-MP) on the current situation in Ukrainian and World Orthodoxy. As a result ten frames (structure, action, aggression, people, values, right, power, territory, religious terms, time orientation) are identified. Frequently used categories are: structures, actions, aggression, people. The scenario of studied statement is constructed: Church, actions, split, believers, unity, rights, patriarchy, path, Lord and year. In general, the statement contains many allegations of unlawful acts, interference with the life of the Church. These accusations directed to the Constantinople Patriarchate, the Orthodox Church of Ukraine and state power of Ukraine. The statement does not call for unity; it contains calls for further confrontation and «correction of errors». The statement contains a request to the authorities to abolish the law on the renaming of the UOC-MP, but in the entire statement, Synod are called themselves as UOC. This misleads ordinary Ukrainians; they do not identify the UOC as a structure subordinated to Russia.